Study of Land Freight Transportation Operation Model In Selected 3t (Frontier, Underdeveloped, & Outermost) Areas, West Papua Province (Empirical Study of South Manokwari, Arfak Mountains, & Wondana Bay Districts) - Hayata, Hayata; Kasman, Kasman; Harjono Padmono Putro (INFOKUM, 2020)
The difference in prices of goods, staples, and goods influential in the pioneer, such as the remote, the outermost border between countries to other areas, is generally relatively high. The availability and stability of prices of goods staples and goods are essential in the Central government subsidies to provide freight in the remote areas, the outermost, and the border (President Regulation Number 71 In 2015 on the determination and storage of goods staple and essential). In The President Regulation Of the Republic Indonesian Number 70 in 2017 on the implementation of an Obligation of publik service for the conveyance of goods to and from disadvantaged, remote, the outermost, and the borders, the meaning of the implementation of public service obligation for the conveyance of goods is the implementation of the transportation of goods to and from disadvantaged, remote, the outermost, and the borders by the latter part of the route, and keep the safety of relating to transportation and security. The government determined the disadvantages in Indonesia in the presidential decree of the Republic of Indonesia no 131 in 2015, which determined the disadvantaged years of 2015-2019, with a district of about 122 runs in Indonesia. However, the disadvantaged will be studying the operation of the model land transportation in the 3T (in front of, left behind, and the outermost) case studies in Papua West. Areas 3T selected a focus in the study model the primary goods transport and important which was in the provinces of west Papua, namely: 1) the outpost, in the south Manokwari; 2) disadvantaged, in the gulf of Wondana; and 3) outermost regions, in the mountains awful. Output activities the conduct of this study in the form of the proposal of a subsidy 3T ( in front of, left behind, and the outermost ), a case study in the West Papua”. Model of Freight Transport Operations in Region 3T 3T (in front of, left behind, and the outermost) is expected to be used in each region by adjusting the Operational Cost Vehicle component (BOK) and the type of goods transport vehicle operating. The research is expected to provide a choice for the subsidies and the form subsidies for the appropriate 3T areas elected in the province of west Papua, particularly in the front of Monokwari South regions, left behind areas in Teluk Wondana regions, and outermost areas in the mountains region Afrak, etc.